Environmental effects of shifting to healthy diets in India: a nationally representative study. (April 2017) - Aleksandrowicz, Lukasz; Green, Rosemary; Joy, Edward J M; Vetter, Sylvia; Harris, Francesca; Story, Matilda; Haines, Andy
Abstract: Background: Food production is a major driver of environmental change, while dietary risks are the leading cause of global disease burden. Dietary shifts in high-income countries can provide benefits for both health and the environment. However, little is known about such options in low-income and middle-income countries, which often face high burdens of both undernutrition and diet-related chronic disease. As an example, we assessed the changes in greenhouse gas emissions, water footprints, and land use, from shifting current nationally representative patterns of Indian food consumption to healthy diets. Methods: Dietary data were derived from a national 2011–12 household expenditure survey. We modelled the changes in consumption of 36 food groups necessary to meet Indian dietary guidelines. These changes were combined with food-specific data for greenhouse gases emissions, calculated using the Cool Farm Tool, water footprints, from the Water Footprint Network, and land use adapted from the UN Food and Agriculture Organisation. Findings: Shifts to healthy diets nationally required a minor increase in calories (3%), with larger increases in fruit (12%) and vegetables (20%). Percentage of calories from fat and protein were adequate. Meeting healthy guidelines marginally increased environmental footprints, between 1–4% for greenhouses gas emissions, water footprint, and land use. However, these national averages masked substantial variation within subpopulations. For example, shifting to healthy diets among those at risk of undernutrition would require increases of 11% in greenhouse gas emissions, 28% in water footprint, and 39% in land use, whereas decreasing environmental effects from those who currently consume above recommended calories. Environmental effects also varied substantially between six major Indian subregions. Interpretation: Providing healthy diets in India, a country of 1·3 billion, might only necessitate slight increases in environmental footprints. However, major efforts could be required to prevent widespread business-as-usual shifts to caloric-intensive and environmentally intensive affluent diets. Funding: Leverhulme Centre for Integrative Research on Agriculture and Health; Wellcome Trust (Our Planet, Our Health programme).